DEVELOPMENT OF NATIONALISM ATTITUDES IN HISTORY LESSON OF 11TH- STUDENT: STUDY CASE IN MADANIA HIGH SCHOOL -PARUNG BOGOR INDONESIA - Priliarachma, Naviri; Kurniawati, Kurniawati; Umasih, Umasih (Jurnal Imiah Pendidikan dan Pembelajaran, 2020)
This research aims to determine the contribution of history lessons to nationalism attitude in the students of grade 11 in Madania High School, Bogor. Besides, it is also to find patterns of character education development in the ideal of learning history, and the last is to find the obstacles faced by the teachers in building the character of Nationalism through learning history. The research was conducted using qualitative methods through in-depth interviews and questionnaires for the students of grade 11 and the history teacher at Madania High School, Parung, Bogor. The Nationalism Attitude is an attitude that shows the balance of love of the people in a country and the harmony of culture and territory contained in a nation to create and will defend the country both internally and externally. The subjects of this research were the history teacher and the students of grade 11 at Madania High School each from The department of Natural Sciences and Social Sciences and the research was conducted during January 2020 through March 2020 school year. The methods used in this research was a qualitative method and using a case study approach. Based on the results of observations and in-depth interviews with the history teacher and the students in grade 11 at Madania High School, it can be concluded by the researcher, the most prominent aspects of Nationalism are attitudes of love the motherland, honesty, responsibility, leadership, cooperation, and tolerance. Also, the 11th-grade students at Madania High School stated that the history teacher performance had been very good and had succeeded in instilling a nationalism attitude through history lessons. Besides, students also suggest for the future history teacher to make history lessons more interesting by adding role-playing lessons when studying a subject in a history book and to add state defending material in history lessons.Keyword: Development, History lessons, Nationalism Attitude